Estudo fitoquímico de Dalbergia ecastophyllum (L.) Taub. (Fabaceae) - Soares, Rafaela dos Santos (2012)
Dalbergia ecastophyllum (L.) Taub. (Fabaceae), popularly known as "rabo-de-bugio" or marmelo-do-mangue", it is a scandentia or semi-prostrate species, commonly found in estuaries, mangroves and dunes. It was observed that the bees collected a red exudate from the surface of the parts area of this species suggesting that this is the botanical origin of the red propolis. This study aimed to contribute to the chemotaxonomical knowledge of the genus Dalbergia and of the family Fabaceae through the phytochemical study of the species D. ecastophyllum. The plant material was collected in Rio Tinto - Paraíba and a voucher specimen was deposited in the Herbarium of the Department of Systematics and Ecology - UFPB with the code 45738 (JPB). For the phytochemical study, the plant material, after drying and pulverization, was subjected to extraction processes, and partition chromatography to isolate the chemical constituents. The chemical structures were determined by spectroscopic methods, such as IR and 1H NMR and 13C one and two-D, and comparisons with models of literature. From the hexane phase, the triterpene friedelin, two mixtures of steroids, non-glycosylated and glycosylated (β-sitosterol and stigmasterol) and a mixture of three triterpenes (lupeol, β-amyrin and germanicol) were obtained. From the dichloromethane phase two isoflavones, biochanin A and 2' - hydroxy - 5' - metoxibiochanin A were isolated and identified , this latter substance is being reported for the first time in the genus, thus contributing to the chemotaxonomy of the genus Dalbergia and family Fabaceae.